2018
DOI: 10.1042/bsr20181183
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between platelet parameters and sudden sensorineural hearing loss: a systematic review and meta-analysis

Abstract: Recent years, the discussion about whether platelets participant in the development of sudden sensorineural hearing loss (SSHL) continues and many studies on the relationship between them have come to our attention. Some studies believe that platelet parameters have significantly changed in patients with SSHL, while some not, controversially. Therefore, to investigate the association between platelet parameters, including mean platelet volume (MPV), platelet distribution width (PDW) and platelet count (PLT), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…A meta-analysis investigating the role of platelet parameters found that SSHL patients present with lower platelet counts. 27 In our present work, low-normal platelet count was a significant independent risk factor for the incidence of LFHI during a long-time span of 5 years. In addition, decreasing platelets surprisingly associates with the loss of hearing ability in low-normal platelet group subjects.…”
Section: Discussionsupporting
confidence: 59%
“…A meta-analysis investigating the role of platelet parameters found that SSHL patients present with lower platelet counts. 27 In our present work, low-normal platelet count was a significant independent risk factor for the incidence of LFHI during a long-time span of 5 years. In addition, decreasing platelets surprisingly associates with the loss of hearing ability in low-normal platelet group subjects.…”
Section: Discussionsupporting
confidence: 59%
“…In the present study, MPV, PDW and PCT values were significantly higher in Group 1 as compared to Groups 2 and 3, whereas there was no significant difference between Groups 2 and 3 ( Table 1 ). Ji et al [ 26 ] reported a meta-analysis and demonstrated that there was no significant difference among the MPV values and between controls. Sun et al [ 27 ] reported an association between MPV values and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The initial search yielded 3,747 results, of which 1,936 were duplicates and removed, leaving 1,811 articles for title and abstract review. Of these 1,811 articles, 68 articles were selected for full-text review against the inclusion and exclusion criteria, which yielded 21 articles [6][7][8][9][10][11][12][32][33][34][35][36][37][38][39][40][41][42][43][44][45] (with 54 outcomes) to be used in the final analysis.…”
Section: Searchmentioning
confidence: 99%